Country-Specific Determinants Of Asean Firms Cross-Border Mergers And Acquisitions (Cbmas) Success - Rahim, Nurhazrina Mat (2019)
Cross-border mergers and acquisitions (CBMAs) are deemed the preferred internationalisation mode with a high preference towards CBMAs by firms, particularly from the ASEAN member countries. Nevertheless, the issue of CBMA success emerges due to high deal failure and non-value creation by firms involved in CBMAs. Thus, it impelled the needs to examine the determinants of CBMA success. The main characteristic of CBMA which is cross-country transaction could risk CBMA success due to country characteristics. Hence, this study chose to focus on the country-specific factors (i.e. country-level corporate governance, exchange rate volatility, cultural distance, geographic distance, and the level of economic development) as determinants of a CBMA success. The scrutinisation of 246 CBMAs involving ASEAN target firms and 348 CBMAs comprising ASEAN bidding firms reveals that the CBMA success rate of ASEAN target firms is slightly higher than ASEAN bidding firms. The long-term market-based performance (Tobin’s Q) of ASEAN target firms improved following CBMA whereas for ASEAN bidding firms, the performance deteriorated. The result from multiple regression analysis was conclusive; country-level corporate governance could affect the success of CBMA for ASEAN firms. The acquisition of ASEAN target firm by a bidder from a country with inferior corporate governance standard could risk the CBMA success due to the negative spillover. Meanwhile, for ASEAN bidder, the possibility of CBMA success increases through positive spillover provided that the governance gap is large and the ownership participation is not too high.